Cyclic tensile strain controls cell shape and directs actin stress fiber formation and focal adhesion alignment in spreading cells - Greiner, Alexandra M.; Chen, Hao; Spatz, Joachim P.; Kemkemer, Ralf (PLOS ONE, 2013)
The actin cytoskeleton plays a crucial role for the spreading of cells, but is also a key element for the structural integrity and internal tension in cells. In fact, adhesive cells and their actin stress fiber-adhesion system show a remarkable reorganization and adaptation when subjected to external mechanical forces. Less is known about how mechanical forces alter the spreading of cells and the development of the actin-cell-matrix adhesion apparatus. We investigated these processes in fibroblasts, exposed to uniaxial cyclic tensile strain (CTS) and demonstrate that initial cell spreading is stretch-independent while it is directed by the mechanical signals in a later phase. The total temporal spreading characteristic was not changed and cell protrusions are initially formed uniformly around the cells. Analyzing the actin network, we observed that during the first phase the cells developed a circumferential arc-like actin network, not affected by the CTS. In the following orientation phase the cells elongated perpendicular to the stretch direction. This occurred simultaneously with the de novo formation of perpendicular mainly ventral actin stress fibers and concurrent realignment of cell-matrix adhesions during their maturation. The stretch-induced perpendicular cell elongation is microtubule-independent but myosin II-dependent. In summary, a CTS-induced cell orientation of spreading cells correlates temporary with the development of the acto-myosin system as well as contact to the underlying substrate by cell-matrix adhesions.
Gesehen am 25.02.2020